Implementation of Occupational Health and Ergonomics in Hospital Workers: A Case Study of Charitas Hospital Palembang - Rusli, Noer Triyanto; Santoso, Harsono (Jurnal Pengabdian Masyarakat Bangsa, 2025)
Background: Hospital employees face higher risks of work-related diseases and injuries compared to other professions. Ergonomic hazards such as repetitive movements, awkward postures, forceful exertion, prolonged static positions, vibration, extreme temperatures, and work stress contribute significantly to musculoskeletal disorders (MSDs), including cervical spasm, low back pain, scoliosis, and carpal tunnel syndrome. At Charitas Hospital Palembang, 2022 medical check-up data reported cervical spasm (0.3%), low back pain (1.6%), scoliosis (0.5%), and carpal tunnel syndrome (0.2%). To promote awareness of ergonomic hazards and preventive strategies among hospital staff and encourage integration of ergonomics into occupational health systems. A hospital-based seminar titled “Implementation of Occupational Safety and Ergonomics in Hospitals” was conducted on April 29, 2023, involving approximately 120 clinical and non-clinical staff. The program consisted of lectures, discussions, and practical examples. Participant feedback was collected through structured evaluations. Over 85% of participants found the material relevant and useful, while 90% expressed satisfaction with the delivery. The seminar demonstrated that even low-cost, short-duration interventions can effectively raise awareness, strengthen safety culture, and improve staff productivity.